2018
DOI: 10.15453/2168-6408.1415
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Therapy Adjunct Faculty Self-Perceptions of Readiness to Teach

Abstract: To meet the demands of a growing profession, occupational therapy (OT) education programs rely on adjunct faculty to augment their faculty pool. Clinicians transitioning into faculty roles frequently do not have formal training in teaching and learning practices. This problem is compounded with adjunct faculty, as they are not using best teaching practices in OT education programs and do not have easy access to university resources. A qualitative study was conducted to describe the perceptions of new OT adjunc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…1 Because many work on a semesterby-semester basis for a few days or hours per week, they face many issues such as the lack of job security, paid leave entitlements, salaries that are based on an hourly formula, and limited access to professional development resources. 15 Additional supports may be needed for contract or parttime faculty, to address their needs, such as developing their pedagogical skills. 15 Although expected to fulfill many roles, the literature supports findings that next-generation academics' foremost responsibility is teaching.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Because many work on a semesterby-semester basis for a few days or hours per week, they face many issues such as the lack of job security, paid leave entitlements, salaries that are based on an hourly formula, and limited access to professional development resources. 15 Additional supports may be needed for contract or parttime faculty, to address their needs, such as developing their pedagogical skills. 15 Although expected to fulfill many roles, the literature supports findings that next-generation academics' foremost responsibility is teaching.…”
Section: Discussionmentioning
confidence: 99%
“…15 Additional supports may be needed for contract or parttime faculty, to address their needs, such as developing their pedagogical skills. 15 Although expected to fulfill many roles, the literature supports findings that next-generation academics' foremost responsibility is teaching. 11 This explains the challenges related to the teaching role: adjustment from clinician to faculty roles, doubting their educator competence, designing effective lectures, exams, and other teaching-learning activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding, together with the responses that a major motivator and benefit of academia was the enjoyment of and opportunity to teach occupational therapy students, supported the premise that some Australian occupational therapy academics prefer to teach rather than pursue a research career. Notably, Lockhart‐Keene and Potvin (2018) found that although new occupational therapy academics felt ready to teach students content knowledge, they were less likely to “fully understand their academic role and have limited access to pedagogical content provided by their academic institutions” (p. 1). Fisher, Dones, Petit‐Frere Naromie, Dillow and Behler (2017) have reported that there is a shortage of qualified educators within the US and challenges recruiting qualified and experienced academic staff.…”
Section: Discussionmentioning
confidence: 99%